2020
DOI: 10.1088/1755-1315/478/1/012080
|View full text |Cite
|
Sign up to set email alerts
|

Some Factors Affecting the Semen Production Continuity of Elite Bulls: Reviewing Data at Singosari National Artificial Insemination Center (SNAIC), Indonesia

Abstract: Singosari National Artificial Insemination Center (SNAIC), East Java is one of the most important Government Institution which produces frozen semen from elite bulls and distributes it to overall Indonesia regions of the most part and to overseas of the other small part. The local elite bulls at SNAIC were originated and selected from the population based on the phenotypic characteristics and pedigrees. While the exotic breed was originated from the certified elite bulls from company in overseas. This paper wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Therefore, the PRM1 concentrations detected in sperm in this study may include genetic factors that influence the high and low semen production detected in LIM, FH, PO, and Aceh bulls (Figure -2). Suyadi et al [30] stated that semen volume, the number of sperm, concentration, and sperm motility affect frozen semen production in bulls. However, abnormal PRM expression will decrease the number, concentration, and motility of sperm [31].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the PRM1 concentrations detected in sperm in this study may include genetic factors that influence the high and low semen production detected in LIM, FH, PO, and Aceh bulls (Figure -2). Suyadi et al [30] stated that semen volume, the number of sperm, concentration, and sperm motility affect frozen semen production in bulls. However, abnormal PRM expression will decrease the number, concentration, and motility of sperm [31].…”
Section: Discussionmentioning
confidence: 99%
“…The semen production increased by increasing the body weight from 260 kg to 784 kg [24,25]. In the tropical country like Indonesia with two main seasons dray and rainy season, Suyadi et al (2020) split the months in the year into four groups, and reported that higher semen production semen of PO cattle was observed higher in the period of Oct -Dec and Apr -Jun than the others [26].…”
Section: Reproduction Traitsmentioning
confidence: 99%
“…The range of semen volume ranged from 4.07-8.79 ml. Suyadi et al [16] stated that the semen volume in Bali bulls was constant from 4.7 to 4.9 ml/ejaculate. Semen volume increases with age [14].…”
Section: Resultsmentioning
confidence: 99%
“…The semen of the Bali bull in this study is included in the criteria for good quality semen because the requirements for good semen are sperm concentrations of more than 500 million/ml [5]. At the same time, the abnormality is higher than Suyadi [16], which is 2.99%. According to Ax et al [5], good spermatozoa abnormality is less than 20%.…”
Section: Resultsmentioning
confidence: 99%